Iniciación al hábito lector y su incidencia en el desarrollo cognitivo de los niños de educación inicial ll en la Unidad Educativa “santa Mariana de Jesús” provincia Bolívar – Ecuador periodo lectivo 2019 - 2020 - Guerrero Allán, Gladys Marlene (2020)
The purpose of this research was to promote the initiation of the habit of reading for cognitive stimulation in children in Initial Education II of the Santa Mariana de Jesús Educational Unit, through a specific space called the "La Victoria de Leer" Baby Library where children, teachers and parents interacted on the basis of predefined activities in a technical proposal based on special attention to early childhood. The methodology used had a quantitative approach, of the quasi-experimental type, with which we proceeded to work with two study groups, a control group and an experimental group where the proposal was applied. The research collected information by means of three instruments, the first one addressed to the parents to know about the promotion of the reading habit at home, the second one a checklist to observe the initial state and the progress of the child in the reading habit and the third one a test called "Caminito" to evaluate the cognitive or neurofunctional development. The results obtained allowed us to know that the strategy applied in the experimental group improved the cognitive development of the children from 0% of children in average condition in the pre-test event to 83% in the post-test event. These results were significantly higher than those of the control group with 0% of children in very low condition initially and 48% in the final data collection. These results were evaluated and statistically proven by means of the t student test, which allowed us to verify that the data had a significance level higher than 95%, which allows us to affirm that the initiation of the reading habit affects the cognitive development of children in Initial II of the "Santa Mariana de Jesús" Educational Unit of the Province of Bolivar. Key words: Cognitive development, reading habit, initial education, neurofunctions.